1
$\begingroup$

The Ellptic\Jacobi theta function is given by \begin{align} \theta_1(\tau|z)&=\theta_1(q,y)=-iq^{\frac{1}{8}}y^{\frac{1}{2}}\prod_{k=1}^{\infty}(1-q^k)(1-yq^k)(1-y^{-1}q^{k-1}) \\ &= -i\sum_{n\in \mathbb{Z}}(-1)^n e^{2\pi i z(n+\frac{1}{2})} e^{\pi i \tau(n+\frac{1}{2})^2} \end{align} Where $q=e^{2\pi i \tau}$, and $y=e^{2\pi i z}$ and dedkind eta function is given as

$\eta(\tau)=\eta(q)=q^{\frac{1}{24}} \prod_{n=1}^{\infty}(1-q^n) $


Now i want to evaluate following relation $\theta'_1(\tau|0)=\theta'_1(q,1)=2\pi \eta(q)^3$

The results is well known (i guess...) but i can not find any papers or textbooks contain some procedure of this.

$\endgroup$
1
$\begingroup$

Rewrite the product in your first equation as $-iq^{1/8}y^{1/2}(1-y^{-1})\prod_{k=1}^{\infty}(1-q^k)(1-yq^k)(1-y^{-1}q^k)$ (just tweak the third part of the product), divide out $(1-y^{-1})$ from the equation, then use L'Hôpital's rule (with respect to $z$ as it approaches $0$) to calculate the limit of the left-hand theta expression; the result you want follows immediately.

You can also substitute $y=e^{2i\pi/3}$ and $q^{1/3}\mapsto q$ to evaluate the Dedekind eta function as a theta function (since $(1-q^{k/3}e^{2i\pi/3})(1-q^{k/3}e^{-2i\pi/3})(1-q^{k/3})=1-q^k$).

As far as I know, I don't think this problem needs residue calculus to solve it, so the title may be misleading.

$\endgroup$
  • $\begingroup$ Thanks for your detail explanation. I will follow your method and re-calculate the computation. $\endgroup$ – phy_math Aug 21 '15 at 4:07
0
$\begingroup$

From Antonio DJC's comment i explicit compute

\begin{align} &\theta_1(q, y)= -i y^{\frac{1}{2}}q^{\frac{1}{8}} \prod_{n=1}^\infty \left(1-q^n\right)\left(1-y q^n\right) \left(1-y^{-1}q^{n-1} \right) \\ &\phantom{\Theta(q,y)}= -i y^{\frac{1}{2}}q^{\frac{1}{8}}(1-y^{-1}) \prod_{n=1}^\infty \left(1-q^n\right)\left(1-y q^n\right) \left(1-y^{-1}q^{n} \right), \\ &\frac{\theta_1(q,y)}{1-y^{-1}}= -i y^{\frac{1}{2}} q^{\frac{1}{8}} \prod_{n=1}^\infty \left(1-q^n\right)\left(1-y q^n\right) \left(1-y^{-1}q^{n} \right) \\ & \lim_{z \rightarrow 0} \frac{\theta_1(\tau|z)}{1-y^{-1}} =\lim_{z \rightarrow 0} \frac{\theta_1'(\tau|z)}{y^{-2} 2\pi i} = \frac{\theta_1'(q,1)}{2\pi i} = -i q^{\frac{1}{8}} \prod_{n=1}^{\infty} (1-q^n)^3 = -i \eta(q)^3 \end{align} where we used $\frac{df(y)}{dz} = \frac{df}{dz} \frac{dy}{dz} = \frac{df}{dz} 2\pi i$. And Dedkind eta function is given as $\begin{align} \eta(q)=q^{\frac{1}{24}} \prod_{n=1}^\infty (1-q^n) \end{align}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.